Small Mammals as Reservoir for Zoonotic Agents in Afghanistan. Issue 1 (4th January 2022) - Essbauer, Sandra; Baumann, Kathrin; Schlegel, Mathias; Faulde, Michael K; Lewitzki, Jens; Sauer, Sabine C; Frangoulidis, Dimitrios; Riehm, J M; Dobler, Gerhard; Teifke, Jens P; Meyer, Hermann; Ulrich, Rainer G
ABSTRACT: Introduction: Rodents and other small mammals can serve as reservoirs for a large number of zoonotic pathogens. A higher risk of infection with rodent-borne pathogens exists for humans with direct contact to rodents and/or their excretions, e.g., soldiers in operation areas. To date, little is known about endemic human pathogenic disease agents that are naturally associated with small mammals in Afghanistan. The aim of this study was to screen abundant rodents and insectivores collected from 2009 to 2012 in four field camps of the German Federal Armed Forces (Bundeswehr) in Northern Afghanistan for the presence of different pathogens. Materials and Methods: Isolated nucleic acids from ear pinna were screened by real-time PCR for spotted fever group (SFG) rickettsiae and from liver samples for Francisella spp., Coxiella burnetii, Brucella spp., Yersinia pestis, and poxvirus. Chest cavity lavage (CCL) samples were tested for antibodies against SFG and typhus group (TG) rickettsiae, as well as against flaviviruses using an indirect immunofluorescence assay. Results: Rickettsial DNA was detected in 7/750 (1%) ear pinna samples with one being identified as Rickettsia conorii . Antibodies against SFG rickettsiae were detected in 15.3% ( n  = 67/439) of the small mammals; positive samples were only from house mice ( Mus musculus ). Antibodies against TG rickettsiae were found in 8.2% ( n  = 36/439) of the samples, with 35 from house mice and one from gray dwarf hamster ( Cricetulus migratorius ). Flavivirus-reactive antibodies were detected in 2.3% ( n  = 10/439) of the investigated CCL samples; again positive samples were exclusively identified in house mice. All 199 investigated liver-derived DNA preparations were negative in the Francisella spp., C. burnetii, Brucella spp., Y. pestis, and poxvirus-specific PCRs. Conclusions: Further investigations will have to prove the potential value of rodents in army camps as sentinel animals.